SMUT FUNGI PARASITIC ON CEREALS IN KASHKADARYA VILOYATE (ORDER USTILAGINALES) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Smut fungi parasitizing cereals in the Kashkadar region (Order Ustilaginales). The article studied the distribution of smut fungi on cereals in the Kashkadar region.